Improving the quality of teacher education for sustainable development of Taiwan's education system: A systematic review on the research issues of teacher education after the implementation of 12-year national basic education - Wang, Ru-Jer; Shih, Yi-Haung (Frontiers in Psychology, 2022)
In this study, the researchers analyzed the issues in teacher education research after the implementation of the 12-Year Basic Education policy and developed suggestions to improve the quality of teacher education in Taiwan. The researchers used Taiwan’s Database of Journal Citations in Science Education to collect studies on teacher education published from 2015 to 2019 and analyzed the issues described therein. 15 categories of issues described therein. Regarding our suggestions for future research on teacher education, this study recommends strengthening the body of literature on the following themes: (1) the professional development of preservice teachers, (2) teacher education for special education, (3) quality assurance for teacher education, (4) the career development of preservice teachers, (5) teacher education for experimental education and rural schools, (6) the sociology of teacher education, and (7) the operation of teacher education centers. Our findings may serve as a reference in efforts to improve the quality of of teacher education, and promoting the sustainable development of Taiwan’s education system.